The use of software in nursing care – Literature review (Research, Society and Development, 2021)
Objective: this article aims to analyze the available database on the use of software in nursing care, as well as cataloging and making available a list of articles aimed at this update on doing health. Methodology: this is a review of the literature, therefore, a search was performed in the periodical databases CAPES and LILACS, published in the last five years and with bibliographic information. In addition, Health Sciences Descriptors (DECS) were used: Softwares; Nursing care; Innovation. Results: scientific articles were found focused on assistentialism and modernization of nursing work, demonstrating that the use of this new way of doing health is in the reality of the nursing team, therefore, there is a need for this team to monitor the pace of evolution according to the needs of the labor market. Final considerations: a greater publication of studies in the area is undoubtedly necessary, so that professionals have more scientific basis on the transformations in the health field, in addition to a greater interest on the part of the nursing team in updating the way of doing health.